Monitoring zearalenone in corn flour utilizing novel self-enhanced electrochemiluminescence aptasensor based on NGQDs-NH2-Ru@SiO2 luminophore. (15th September 2019) - Luo, Lijun; Ma, Shuai; Li, Libo; Liu, Xiaohong; Zhang, Jiayi; Li, Xia; Liu, Dong; You, Tianyan
Highlights: A novel self-enhanced ECL Ru(II)-complex was firstly synthesized. Luminophor (NH2 -Ru@SiO2 ) and co-reactant (NGQDs) existed in the same nanoparticle. An effective monitoring method for ZEN was developed by the developed aptasensor. ZEN produced during the mildew process of corn flour was monitored. Results exhibited superior determination and potential application in real samples. Abstract: Accurate and early diagnosis of mycotoxin is particularly significant to the food and agricultural product safety. In the present work, a sensitive and effective monitoring method for zearalenone (ZEN) was exploited based on a novel self-enhanced electrochemiluminescence (ECL) aptasensor. The self-enhanced lumonophore was compounded by electrostatically combining amine-functionalized Ru(bpy)3 2+ -doped silica nanoparticles (NH2 -Ru@SiO2 NPs) and nitrogen doped graphene quantum dots (NGQDs) together. Since the emitter and co-reactant simultaneously existed in the same nanoparticle, shortened electron-transfer distance and decreased energy loss was obtained. Therefore, self-enhanced ECL aptasensor based on the novel complex expressed the widest linear range of 10 fg mL −1 –10 ng mL −1 and the lowest detection limit of 1 fg mL −1 for ZEN detection. More importantly, ZEN produced during the mildew process of corn flour was monitored by the developed aptasensor, which exhibited superior determination and potential application in real samples.